Improving Animal Production, Productivity and Economic Gain to the Farmers through Increasing Coverage of Artificial Insemination in India - Prasad, Shiv; Kumar , Sunil (The Indian Journal of Animal Reproduction, 2022)
Data from authentic sources i.e. Government Annual Reports, published research papers and various cooperative organizations of the country were collected and analyzed using ARIMA (Auto Regressive Integrated Moving Average), ADF (Augmented Dickey-Fuller Test) to arrive at definite conclusions for the scientific fraternity in the field of Animal Reproduction. The sole objective for giving information is to get the momentum of developmental activities further in one of the most important technologies i.e. Artificial Insemination (AI) which has changed the country from a milk deficit to a milk surplus and taken the nation on top of the milk producing countries of the world with 209.9 million tones followed by USA, Pakistan, China and Brazil. Presently India is performing 81.9 million AI’s annually with a lower conception rate of about 35% in 2021. Per capita milk availability per day, Productivity, AI coverage, Expansion of AI, Conception rate, Milk production growth rate, Milk processing status, Milk prices and Farmer’s gain per litre of milk produced have been 427 ml, 5.65 litres, 30%, 16 million farmers, 35%, 5.8%, 20.50% of the total milk produced in the country, Rs 35/litre for cows and Rs.52 /litre for buffaloes, respectively. Hence, the profitability of the fluid milk for farmers is negligible considering the current market infrastructure in the country. It is concluded from the study that the AI programme must be continued in campaign mode till it reaches about 80% of the breedable bovine population with a continuous programme of producing High Genetic Merit (HGM) bulls in the country and their availability to semen stations for semen production which will answer the future need of the nation.
Keywords: ARIMA; ADF; Artificial Insemination; Breedable; HGM